Philadelphia, June 1876 Paper - Water in Coals - J. Blodget Britton (The American Institute of Mining, Metallurgical, and Petroleum Engineers)
SIX different samples of anthracite, each a firm compact lump, were finely pulverized and immediately put in bottles. Portions of these were weighed and placed upon an ordinary water-bath and dried for one hour; the average loss was 1.24. The same portions were then placed in a hot-air oven, and for two hours kept at a temperature of 285' F., and, after cooling in a dry chamber, were again weighed, when there was found a further average loss of 1.22, making a total so far of 2.46. They were then immediately returned to the oven and for two hours more kept at a temperature of 530' F. and cooled and weighed again, when no further loss was found, but an average gain of .55 upon the previous weighing. The same portions were a third time placed in the oven and for about ten minutes kept at the last-mentioned temperature, and then, while still hot, were poured into one-quarter inch glass tubes, each with a bulb at one end, and heated over a Bunsen burner at a temperature below a red heat, when more water vaporized and condensed in small clear globules on the cold parts of the tubes. Fresh portions of the coals were then taken, and the total amount of water determined, and the average was found to be 3.04, or 1.80 more than was found at the temperature of the water-bath, which was perhaps a little below 212' F., and .58 more than at 285' F. Tests were afterwards made by placing other fresh portions of the